Estudos de parâmetros de qualidade para cerâmica estrutural vermelha - Paschoal, José Antonio Armani (2003)
Civil construction demands quality in terms of reduction of waste and costs. Red ceramic, bricks and tiles have been targets in this effort. The Quality Programs seek to certify ceramics within norms (NBR ISO 9000), whose objectives are the controls demanded for these products. INMETRO and the agent of certification, Ceramic Center of Brazil (CCB), enforce, by means of laboratory analyses, the ceramic product of certified businesses. This work aims to evaluate the quality control system and manufacturing process of red ceramic tile, contributing to micro and small businesses by completing laboratory analyses of raw materials and end products of industries that present difficulties in terms of such controls. By means of a diagnostic fluxogram, evaluating and orientating, the operation of the process is optimized in full or in part. Of the 12 businesses utilized, distributed among 4 regions of the state of São Paulo, 3 were certified in the Quality System, 3 in the certification process, and 6 still uninitiated. The results found indicate the importance of the Quality System in businesses that have the adopted the norms, for which they have efficient controls, in terms of product conformity and reduction of waste. The raw materials of the state of São Paulo are of good quality for ceramic tiles and require only technological accompaniment. From these completed analyses it was possible to develop a diagnostic fluxogram that permits evaluation of quality and the production process, to be inserted in a "Palm Top", where electronically it can be applied promptly at each step of fabrication.